Interactions of fibronectin with Treponema pallidum. Issue 3 (June 1985) - Fitzgerald, T J; Repesh, L A
Abstract : The adhesive or opsonic glycoprotein, fibronectin, is associated with the surface of Treponema pallidum as shown by immunofluorescence. A quantitative assay using iodine-125 (125I) showed that T pallidum harvested seven days after infection bound more fibronectin than T pallidum harvested 14 days after infection. This increased binding by "younger" organisms was confirmed by radioimmunoassay techniques. Fibronectin appears to have a role in treponemal attachment. Preincubation of T pallidum with goat or rabbit antibody to fibronectin blocked treponemal attachment to cultured cells and to isolated capillaries and inhibited treponemal virulence. Treponemes were incubated in glass wool columns pretreated with fibronectin and were then eluted from the columns. This technique yielded a population of T pallidum that failed to bind to fibronectin. Compared with treponemes eluted from control ovalbumin columns, organisms eluted from fibronectin columns attached to cultured cells in larger numbers but did not survive as long and were not as virulent. Findings are discussed in terms of the relevance of interaction between treponemes and fibronectin in the pathogenesis of T pallidum.